2015
DOI: 10.1016/j.jcm.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lumbosacral Manipulation on Isokinetic Strength of the Knee Extensors and Flexors in Healthy Subjects: A Randomized, Controlled, Single-Blind Crossover Trial

Abstract: Objective: The purpose of this study was to investigate the effect of manual manipulations targeting the lumbar spine and/or sacroiliac joint on concentric knee extension and flexion forces. Torque production was measured during isometric and isokinetic contractions. Methods: This was a randomized, controlled, single-blind crossover design with 21 asymptomatic, college-aged subjects who had never received spinal manipulation. During 2 separate sessions, subjects' peak torques were recorded while performing max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…We included 20 articles with a low risk of bias, of which seven were randomized controlled crossover studies [30, 31, 35, 4143, 46], 10 were randomized controlled trials (RCT) [13, 14, 3234, 3739, 44, 47] and three were RCT pilot studies [36, 40, 45].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We included 20 articles with a low risk of bias, of which seven were randomized controlled crossover studies [30, 31, 35, 4143, 46], 10 were randomized controlled trials (RCT) [13, 14, 3234, 3739, 44, 47] and three were RCT pilot studies [36, 40, 45].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported on adverse events [30, 36, 40, 44]. Four studies reported on physiological outcomes [30, 33, 42, 47], 16 studies reported on biomechanical outcomes [13, 14, 31, 3446], three of which also reported on sport-specific outcomes [40, 42, 45], and one additional study reported on performance variables for specific sports [32, 42].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations